Cyclophosphamide‐induced cardiotoxicity at conditioning for allogeneic hematopoietic stem cell transplantation would occur among the patients treated with 120 mg/kg or less. Issue 5 (14th March 2022) - Marumo, Atsushi; Omori, Ikuko; Tara, Shuhei; Otsuka, Yuki; Konuma, Ryosuke; Adachi, Hiroto; Wada, Atsushi; Kishida, Yuya; Konishi, Tatsuya; Nagata, Akihito; Yamada, Yuta; Nagata, Ryohei; et al.
Abstract: Cyclophosphamide (CY)‐induced cardiotoxicity involves rare lethal complications. We previously reported the cardiac events of 811 allogeneic hematopoietic stem cell transplant (allo‐HSCT) recipients; 12 out of 811 recipients (1.5%) developed fatal heart failure. The mortality rate was also very high (91.6%, 11/12). CY dose (200 mg/kg or more) was reported as the independent risk factor. The main disease in patients treated with 200 mg/kg or more of CY was severe aplastic anemia (AA). Therefore, we reduced the dose of CY during conditioning for AA (from 200 to 100 mg/kg), and then we analyzed the clinical features of 294 patients who received a total dose of at least 100 mg/kg of CY. We also compared the clinical features between the current study and our previous study. The proportion of patients treated with at least 200 mg/kg of CY was reduced from 4.2% to 0%. However, CY‐induced heart failure occurred in four of the 294 patients (1.4%), which was similar to the finding reported in our previous study (1.5%). Two of these four patients received a post‐transplant CY (PTCy) regimen (CY 100 mg/kg). All four patients were treated in the cardiac intensive care unit (C‐ICU), and two patients survived. In summary, even the CY dose of 120 mg/kg or less would cause cardiotoxicity. We should also carefully monitor patients treated with PTCy, considering the possibility of CY‐induced cardiotoxicity. Early diagnosis and ICU management have contributed to improved outcomes.